PEMAHAMAN KONSEP FIQH IBADAH MELALUI MEDIA INFOGRAFIS BAGI PESERTA DIDIK KELAS IX DI MTsN 2 BANJARMASIN - M. Ramli M. Ramli (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2026)
This study aims to describe students' understanding of the concept of Islamic jurisprudence (fiqh) of worship through infographics, analyze the extent to which these media aid students' understanding of the concept, and identify supporting and inhibiting factors in its use in ninth-grade students at MTsN 2 Banjarmasin. This study is field research with a descriptive qualitative approach. Data collection was conducted through observation of learning activities, in-depth interviews with Fiqh teachers and students, and documentation in the form of learning tools and infographics. Data analysis used data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that: (1) students' understanding of the concept of Islamic jurisprudence (fiqh) of worship through infographics through infographics was achieved through the planning stage by developing a visual-based lesson plan, the implementation stage by presenting the material through digital/printed infographics, and the evaluation stage. (2) Infographics have been proven to aid students' understanding of the concept because they are able to systematically link naqli arguments with worship procedures through the aid of graphic elements. (3) Supporting factors include the availability of technological facilities in madrasas and teacher creativity, while the main challenge lies in the limited time in creating comprehensive infographic designs and variations in the speed of visual literacy between students.